2005
DOI: 10.1007/s10680-005-6856-1
|View full text |Cite
|
Sign up to set email alerts
|

Child Survival and Fertility of Refugees in Rwanda

Abstract: In the 1960s and 1990s, internal strife in Rwanda has caused a mass flow of refugees into neighbouring countries. This article explores the cumulated fertility of Rwandan refugee women and the survival of their children. To this end, we use a national survey conducted between 1999 and 2001 and covering 6,420 former refugee and non-refugee households. The findings support old-age security theories of reproductive behaviour: refugee women had higher fertility but their children had lower survival chances. Newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Bundervoet and Verwimp (2005) find that civil war and economic sanctions affected the anthropometric outcomes of children living in rural Burundi. In the context of Rwanda, Verwimp and Bavel (2005) find that refugee women had higher fertility but their children also had lower chances of survival. Akresh et al (2007) find that girls born in regions of Rwanda affected by crop failure and strife have lower height-for-age z-scores.…”
Section: Introductionmentioning
confidence: 94%
“…Bundervoet and Verwimp (2005) find that civil war and economic sanctions affected the anthropometric outcomes of children living in rural Burundi. In the context of Rwanda, Verwimp and Bavel (2005) find that refugee women had higher fertility but their children also had lower chances of survival. Akresh et al (2007) find that girls born in regions of Rwanda affected by crop failure and strife have lower height-for-age z-scores.…”
Section: Introductionmentioning
confidence: 94%
“…WHO 2002). For instance, Verwimp and van Bavel (2004) show that although refugee women tend to have higher fertility rates than other population groups, their children (girls in particular) have a much lower probability of survival due to the health and socio-economic conditions experienced in refugee camps. These effects are often aggravated by a variety of factors, even after the end of the initial conflict.…”
Section: Changes In Household Compositionmentioning
confidence: 99%
“…The refugee problem contributed to a worsening of health outcomes. Verwimp and Bavel (2005) find that refugee women in Rwanda had higher fertility and their children had lower chances of survival. Another study found that girls born in regions of Rwanda affected by crop failure and strife have lower height-for-age z-scores (Akresh et al 2007).…”
Section: Introductionmentioning
confidence: 81%